A proportional integral estimator-based clock synchronization protocol for wireless sensor networks. (November 2017) - Yang, Wenlun; Fu, Minyue
Abstract: Clock synchronization is an issue of vital importance in applications of WSNs. This paper proposes a proportional integral estimator-based protocol (EBP) to achieve clock synchronization for wireless sensor networks. As each local clock skew gradually drifts, synchronization accuracy will decline over time. Compared with existing consensus-based approaches, the proposed synchronization protocol improves synchronization accuracy under time-varying clock skews. Moreover, by restricting synchronization error of clock skew into a relative small quantity, it could reduce periodic re-synchronization frequencies. At last, a pseudo-synchronous implementation for skew compensation is introduced as synchronous protocol is unrealistic in practice. Numerical simulations are shown to illustrate the performance of the proposed protocol. Abstract : Highlights: A PI estimator-based clock synchronization protocol is proposed for WSNs. Synchronization error of skews can be bounded into a relative small steady state. EBP can improve synchronization accuracy under time-varying clock skew.